Robot-Assisted Removal of a Broken Scalpel Blade following Discectomy - Christos Koutserimpas; Argyrios Ioannidis; Michael Konstantinidis; Panagiotis Athanasopoulos; Fotios Antonakopoulos; Konstantinos Konstantinidis (Case Reports in Surgery)
The risk of a broken scalpel blade during discectomy is considered extremely rare, while no guidelines exist regarding this complication. We report a case of a robotic broken blade removal following lumbar discectomy. A 52-year-old female was subjected to L4-L5 discectomy. During the annulus resection, the scalpel blade broke and was retained within the disc space. The broken blade migrated towards the abdominal cavity and viscera. Emergency CT angiography scan revealed that the main vessels were intact, while the broken surgical knife was located anterior to the lumbar spine at the L4/L5 level, to the left of the aorta and superiorly of the left common iliac artery. At that point, robot-assisted laparoscopy was performed. The broken instrument was located and carefully removed. It seems more proper that such foreign bodies should be removed, while robotic surgery may play a significant role in cases that the foreign body is near major vessels.